2011
DOI: 10.5251/ajsir.2011.2.2.283.296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pitting corrosion for aluminum alloys 7020 in 3.5% NaCl solution with range of temperature (100-500) °C

Abstract: The effect of homogenous heating variables (temperature and time holding) on the tendency of high strength Al-alloys type 7020 is investigated. The experiments were carried out by heating the specimens at different temperatures (100, 150, 200, 250, 300, 350, 400, 450 and 500) °C for two periods of holding time (one hour and two hours). Microstructure of an alloy was investigated by the optical microscope before and after heating at each temperature and precipitation phase and clearing revealed MgZn 2 . An imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…For all samples, it can be observed that pitting initiation cites are having correlation with cites of intermetallic precipitates and greatly affected by their distribution and size. Such observation was also observed by Mosleh et al [12], Alsamuraee et al [18], and Bousquet et al [19]. This observation suggests the formation of corrosion cells where the precipitates, of less Ecorr, acts as a sacrificial anode to the Al matrix, of higher Ecorr.…”
Section: Corrosion Behaviorsupporting
confidence: 72%
See 3 more Smart Citations
“…For all samples, it can be observed that pitting initiation cites are having correlation with cites of intermetallic precipitates and greatly affected by their distribution and size. Such observation was also observed by Mosleh et al [12], Alsamuraee et al [18], and Bousquet et al [19]. This observation suggests the formation of corrosion cells where the precipitates, of less Ecorr, acts as a sacrificial anode to the Al matrix, of higher Ecorr.…”
Section: Corrosion Behaviorsupporting
confidence: 72%
“…Precipitation hardening for the T4-condition samples was achieved by natural ageing at room temperature for more than 30 days to reach a stable condition [5]. For the T6-condition samples, precipitation hardening was achieved by artificial ageing at 165±5 o C for 10 hours to obtain optimum strength as reported by Wojcirch [18]. A sample from each experiment trial was cut for microstructure investigation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrid composite shows lowest I corr due to formation of oxide film and presence of low percentage of graphite particles being anodic to the matrix [8,28,29].…”
Section: Effect Of Nacl Medium On the Corrosionmentioning
confidence: 99%